Rust en stilte in de kunst. - Vanderberghe, Françoise; Brutin, Hugo; Orion Art Gallery, Oostende (Oostende : Orion Art Gallery, 2000)
Decock, Gilbert ; Delbrassine, Elise ; De Mey, Gaston ; Dusepelchre, Francis ; Dries, Jan ; Maury, Jean-Pierre ; Swimberghe, Gilbert ; Vanderbranden, Guy ; Vandoorslaer, Etienne ; Vansumere, Hilde ; Verstockt, Mark ; Wuidar, Léon
Orion Art Gallery, Oostende, 15.10.2000 - 14.01.2001
kunstcatalogus